Factors impacting bicyclist lateral position and velocity in proximity to commercial vehicle loading zones: Application of a bicycling simulator. (April 2019) - Abadi, Masoud Ghodrat; Hurwitz, David S.; Sheth, Manali; McCormack, Edward; Goodchild, Anne
Graphical abstract: Highlights: A Full-scale bicycling simulator was used to study bicycle-truck interactions. Truck Maneuver had the largest effect on bicyclist velocity and lateral position. Solid green pavement marking reduced bicyclist velocity and decreased divergence from right-edge of bicycle lane. Warning sign increased bicyclist divergence from right-edge of bicycle lane. Of 288 simulated conflicts between bicyclists and exiting trucks, four crashes occurred. Abstract: There is little research on the behavioral interaction between bicycle lanes and commercial vehicle loading zones (CVLZ) in the United States. These interactions are important to understand, to preempt increasing conflicts between truckers and bicyclists. In this study, a bicycling simulator experiment examined bicycle and truck interactions. The experiment was successfully completed by 48 participants. The bicycling simulator collected data regarding a participant's velocity and lateral position. Three independent variables reflecting common engineering approaches were included in this experiment: pavement marking (L1: white lane markings with no supplemental pavement color, termed white lane markings, L2: white lane markings with solid green pavement applied on the conflict area, termed solid green, and L3: white lane markings with dashed green pavement applied on the conflict area, termed dashed green), signage (L1: No sign and L2: a truck warning sign), and truck maneuver (L1: no truck in CVLZ, L2: truck parked in CVLZ, and L3: truck pulling out of CVLZ). The results showed that truck presence does have an effect on bicyclist's performance, and this effect varies based on the engineering and design treatments employed. Of the three independent variables, truck maneuvering had the greatest impact by decreasing mean bicyclist velocity and increasing mean lateral position. It was also observed that when a truck was present in a CVLZ, bicyclists had a lower velocity and lower divergence from right-edge of bike lane on solid green pavement, and a higher divergence from the right-edge of bike lane was observed when a warning sign was present.